Effects of divergent selection for seed protein content in high‐protein vs. food‐grade populations of early maturity soybean. Issue 1 (13th December 2013) - Sato, Takashi; Van, Melanie; Wagentristl, Helmut; Vollmann, Johann; Singh, R.
Abstract Due to the growing need for vegetable protein in Central European agriculture, there is interest in producing food‐grade soybeans, which are higher in seed protein and sucrose content and have a larger seed size than conventional soybeans. As protein content of conventional soybean is often below 400 g/kg, either high‐protein or food‐grade donors were crossed with adapted genotypes in order to increase their protein level. After divergent selection for protein content, lines were evaluated for seed quality characters across three environments in Austria. The objectives of this research were to determine the roles of genetic background and the selection for protein content on food‐grade soybean traits. While seed protein content of adapted parents was between 395 and 420 g/kg, its range was from 410 to 490 g/kg for the high‐protein and from 390 to 450 g/kg for the food‐grade lines, respectively. However, food‐grade populations were superior in seed size and sucrose content and revealed different correlation patterns between quality traits as compared to high‐protein populations, which demonstrates their usefulness for developing soybeans with improved quality.